2011
DOI: 10.5657/fas.2011.0389
|View full text |Cite
|
Sign up to set email alerts
|

Macroalgal Community Structure on the Rocky Shores of Ongdo, Jusamdo, and Woejodo Islands of the Yellow Sea, Korea

Abstract: The benthic algal community structures of the seaweed biomass, vertical distribution of dominant seaweeds, and species composition were examined on the rocky shores of Ongdo, Jusamdo, and Woejodo Islands, Korea, in August 2006. A total of 68 seaweeds were identified, comprising 5 green, 11 brown, and 52 red algae from the three study sites. The number of species at Ongdo (32 species) was less than that at Jusamdo (45 species) and Woejodo (44 species). Jusamdo exhibited the maximum seaweed biomass (73.99 g dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The highest level of these patterns is generally found at mean low water (MLW) and decreases with both increasing depth and intertidal height (Garrabou et al 2002, Choi and Kim 2004, Kang and Kim 2004, Balata et al 2006, Konar et al 2009. Although numerous studies have described these general zonation patterns, recent studies have suggested that these patterns may not be generalizable across geographic regions because peaks in abundance or diversity are not found consistently in particular depth strata (Balata and Piazzi 2008, Konar et al 2009, Heo et al 2011, Kang et al 2011. Therefore, there is great interest in investigating not only these exceptional patterns but also different zonation patterns in species composition, diversity, abundance, and community dynamics among areas at local scales (Konar et al 2009, Heo et al 2011, Kang et al 2011, Shin et al 2011.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The highest level of these patterns is generally found at mean low water (MLW) and decreases with both increasing depth and intertidal height (Garrabou et al 2002, Choi and Kim 2004, Kang and Kim 2004, Balata et al 2006, Konar et al 2009. Although numerous studies have described these general zonation patterns, recent studies have suggested that these patterns may not be generalizable across geographic regions because peaks in abundance or diversity are not found consistently in particular depth strata (Balata and Piazzi 2008, Konar et al 2009, Heo et al 2011, Kang et al 2011. Therefore, there is great interest in investigating not only these exceptional patterns but also different zonation patterns in species composition, diversity, abundance, and community dynamics among areas at local scales (Konar et al 2009, Heo et al 2011, Kang et al 2011, Shin et al 2011.…”
Section: Introductionmentioning
confidence: 87%
“…Clear differences were observed in the composition of dominant macroalgal species and vertical distribution when compared with other sites along the Korean peninsula. Communities at Jusamdo in the Yellow Sea are characterized by Desmarestia ligulata at subtidal depths of 5 m and vertically broad distributions of S. thunbergii (Heo et al 2011); Daejin communities in the East Sea are marked by Symphyocladia latiuscula and Phyllospadix japonicus (Shin et al 2011). These differences were probably due to several factors particular to each local region, such as annual mean sea surface temperature, difference in tidal level, latitude, hydrodynamics, topography, or turbidity (Chung et al 1998, Kim et al 1998, Stewart and Carpenter 2003, Kang et al 2011 macroalgal assemblages near the MLW indicates that the macroalgal assemblages changed dramatically with season closer to the MLW, whereas assemblages in the higher intertidal and deeper subtidal zones were more stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. crassa had filamentous thalus that can withstand environmental stress. This species is also known to be able to live on saltwater or freshwater, has a high salinity tolerance and high reproductive capability (Heo et al, 2011). Glacilaria edulis and Gelidiella acerosa is economically important red algae.…”
Section: Resultsmentioning
confidence: 99%
“…This is indicated by the results that E. intestinalis was the most abundance species (0,30 ind/m 2 ), then U. fasciata (0,28 ind/m 2 ), and C. catenata (0,22 ind/m 2 ). The filamentous forms of macroalgae are generally stress-tolerant species, able to live on saltwater or freshwater (Wong et al, 2011) and high reproductive capability (Heo et al, 2011). Species such as Halimeda sp.…”
Section: Resultsmentioning
confidence: 99%